1996
DOI: 10.1128/aac.40.9.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human cytomegalovirus immediate-early gene expression by an antisense oligonucleotide complementary to immediate-early RNA

Abstract: ISIS 2922 is a phosphorothioate oligonucleotide that is complementary to human cytomegalovirus (CMV) immediate-early (IE) RNA and that exhibits potent and specific antiviral activity against CMV in cell culture assays. Specific assay systems were developed to separately characterize the antisense and nonantisense components of the antiviral activity mediated by ISIS 2922. In U373 cells transformed with cDNA encoding the CMV IE 55-kDa (IE55) protein, expression was inhibited at nanomolar concentrations comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(59 citation statements)
references
References 25 publications
0
59
0
Order By: Relevance
“…The antiviral effects of ganciclovir, ISIS 2922, ISIS 26062, SN50, and SN50M were tested in confluent cultures of retinal glial cells infected with the AD169 strain at an MOI of 2. Treatment with ISIS 2922 or ISIS 26062 was performed according to established protocols [30][31][32]. Briefly, cell monolayers were pretreated with oligonucleotides at different concentrations overnight in MEM containing 2% FBS and then were washed 3 times with PBS before virus infection.…”
Section: Methodsmentioning
confidence: 99%
“…The antiviral effects of ganciclovir, ISIS 2922, ISIS 26062, SN50, and SN50M were tested in confluent cultures of retinal glial cells infected with the AD169 strain at an MOI of 2. Treatment with ISIS 2922 or ISIS 26062 was performed according to established protocols [30][31][32]. Briefly, cell monolayers were pretreated with oligonucleotides at different concentrations overnight in MEM containing 2% FBS and then were washed 3 times with PBS before virus infection.…”
Section: Methodsmentioning
confidence: 99%
“…A recent report described that repetitive motifs in telomeric DNA of mammals can suppress Th1 responses of the immune response by interference with the IFN-γ signalling [30]. Indeed, it was shown that the efficacy of ASON is often a mixture of diverse effects [1]. Unwanted side effects of ASON are known to be concentration-dependent [18], but for this model already very small amounts were effective to improve HSK.…”
Section: Discussionmentioning
confidence: 98%
“…Antisense oligonucleotides research is considered a very promising technology for use in the development of drugs with both high target specificity and reduced side effects. Studies have demonstrated antisense inhibition of viral gene expression in biochemical assays, in cultured cells and in animal models [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Currently, there is ongoing antisense oligonucleotides research targeting human cytomegalovirus and human immunodeficiency virus, which is being evaluated in clinical trials.…”
Section: Delivery Of Antisense Therapymentioning
confidence: 99%
“…A targeted novel approach of delivering antisense therapy and other entities which are typically too problematic to deliver may be instrumental. Therefore achieving a combination of targeted delivery of oligonucleotides, other genetic disrupters and other viral targets not normally feasible with current systems may be advantageous [31,32,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102].…”
Section: Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation